Human iPSC-Derived Neuron and Oligodendrocyte Co-culture as a Small-Molecule Screening Assay for Myelination - Stefanie Chie; Zsofia Szentpetery; Melanie Generali; Tanja Kuhlmann; Giancarlo Natalucci; Maria Miletta (Bio-Protocol)
Neurons and oligodendrocytes are the building blocks of the brain. Neurons form synaptic connections and transmit signals, while oligodendrocytes, including oligodendrocyte precursor cells (OPCs) and their derivatives, are vital for central nervous system maintenance and myelination. The demand for human-specific neuron-oligodendrocyte model systems to study these interactions has grown, yet co-culture protocols remain limited. Recent advancements in the field provide methods for deriving co-cultures of neurons and OPCs from human induced pluripotent stem cells (hiPSC), each with distinct benefits and challenges. This study presents a time-efficient, reproducible method to derive neurons and O4-expressing oligodendrocytes, followed by a straightforward co-culture system that minimizes astrocyte differentiation and ensures robust neuron and oligodendrocyte populations.